Reframing humans in information systems development - Isomäki, Hannakaisa; Pekkola, Samuli (Computer supported cooperative work., 2011)
Modern society has been transformed by the digital convergence towards a future where technologies embed themselves into the fabric of everyday life. This ongoing merging of social and technological infrastructures provides and necessitates new possibilities to renovate past notions, models and methods of information systems development that accommodates humans as actors within the infrastructure. This shift introduces new possibilities for information systems designers to fulfill more and more everyday functions, and to enhance their value and worth to the user. Reframing Humans in Information Systems Development aims to reframe the phenomenon of human-centered development of information systems by connecting scientific constructs produced within the field of information systems which has recently provided a plethora of multidisciplinary user views, without explicitly defining clear constructs that serve the IS field in particular. IS researchers, practitioners and students would benefit from Reframing Humans in Information Systems Development as the book provides a comprehensive view to various human-centered development methods and approaches. The representatives of the fields of Human-Computer Interaction and Computer Supported Collaborative Work will also find this book an excellent resource. A theoretical handbook and collection of practical experiences, are included along with critical discussions of the utilization methods in ISD and their implications with some interconnecting commentary viewpoints.